Australian Southern bluefin tuna farming and research activity: National report - Montague P. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
An overview is provided showing how Australian research on the biology and culture of tuna has grown in scope and intensity in step with the successful development of the farming of Southern Bluefin Tuna in South Australia. The nature, progress and future directions are summarized for research on tuna feeds, product quality, environmental management, health and hatchery propagation. Some of the practical problems are discussed, and the approach to coordination of research and industry development is briefly outlined.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)